Satisfaction and Stress in Teachers by Cause of Remote Activities due to COVID-19 contingency - Robles-Ojeda, Francisco Javier (2023)
Objective. This study aims to identify stress, satisfaction, and willingness to continue using technological tools, as well as the main physical and emotional affections when carrying out distance learning activities presented by a sample of teachers of the primary, middle, and high school levels, as well as higher education, that taught distance learning in Mexico. Method. It was based on a non-experimental, cross-sectional, and comparative design. A questionnaire made in Google Forms was administered to 122 teachers. Results. The main results show that 25% of the sample presents low satisfaction; 30% show stress when carrying out their activities remotely; and 40% do not offer a willingness to continue using technological tools for their classes, being the schools of basic level the most affected. The main physical affections referred to were muscle aches, headaches and sleep problems, and emotional conditions related to anxiety, sadness, fear, and uncertainty. Conclusions. It is suggested to develop programs to identify and support the emotional affections of the teaching staff due to their remote work.